Abnormal colour pattern in a wild specimen of Cnemidophorus from the lacertoides species group (Squamata, Teiidae) - Cabrera, Mario Roberto (2012)
The occasional presence of individuals with colour pattern very different from typical is a well known fact in different Squamata (Ballinger and McKinney, 1968; Andrade and Abe, 1998; Carreira, Meneghel and Achaval, 2005), but in many cases still remains not satisfactorily explained (Lema, 1987). It has been interpreted as an anomaly, although it may encompass a significant proportion of the population (Ballinger and McKinney, 1968). In this note we report the finding of an individual of Cnemidophorus from the lacertoides species group (sensu Cei, 1993) exhibiting a pattern different to any other known species from this group (i.e., C. charrua, C. lacertoides, C. leachei, C. serranus and C. vacariensis)...